Toxic Discourse: Waste Heritage as Ghetto Pastoral - Fletcher, Alana (Studies in Canadian Literature, 2014)
This paper undertakes the first ecocritical reading of Waste Heritage, building on discussions of space, mobility, and immobility in the novel in recent work by Colin Hill, Jody Mason, and Candida Rifkind. Waste Heritage, this article argues, employs what Lawrence Buell has called “toxic discourse”: a mode of writing that inculcates environmental awareness through images of toxified spaces, places, and bodies. The toxic discourse of the novel signals its affinity with a group of mostly American works that have been called “ghetto pastorals.” While Waste Heritage is not the classic tale of growing up poor that ghetto pastoral usually connotes, like these works it employs disrupted, invaded, and polluted pastoral imagery to critique a capitalist system in which working-class aspirations toward living wages, suburban life, and leisure space are futile. This article provides a much-needed analysis of how complex pastoral relies on toxic discourse, and models this relationship through a reading of the toxic pastoralism apparent throughout Waste Heritage.